Tanggung Jawab Perusahaan PT. Perkebunan Nusantara V Sei Buatan Terhadap Penerapan Corporate Social Responsibility (CSR) dalam Pencegahan Kebakaran Hutan di Kabupaten Siak Provinsi Riau - Nabila, Khaifa; Firdaus, Firdaus; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia defines CSR as a legal obligation, specifically regulated in laws thatoblige every company to implement CSR. As a legal obligation, companies must complywith the existing relus of the law without exception. CSR is a company to implement CSR.As legal obligation, companies must comply with the existing rules of the law withoutexception. CSR is a company obligation that must be implemented in accordance withArticle 74 of Law Number 40of 2007 concerning limited liability companies. Based ondata from the Riau Regional Disaster Management Agency (BPDB), it is known that inearly 2020 there were three regions that were already on alert status due to forest andland fires. The largest area that experienced forest and land fires is Siak District, with aburned area of more than 100 ha. These forest and land fires habe an impact on thedestruction of ecosystems and disruption of the activities and health of the surroundingcommunities where the forest and land fires occur. Prevention and control of land andforest fires is the responsibility of all elements of society, including companies in theplantation and agriculture sectors. One way is by implementing CSR in the prevention ofcorporate forest fires.This type of research used by the author is sociological legal research, which isstudy of the effectiveness of the current law. Sociological research is research that looksat law with society and is descsriptive in nature, which provides data about humans,conditions or other symptoms, so that it can help between knowing old theories o in rheframework o fcompiling new theories.The purpose of this research is to see whether the implementation of CorporateSosial Responsibility (CSR) by PT. Perkebunan Nusantara V Sei Artifical in preventingforest fires can minimize the rate of forest and land fires in Siak Regency in preventingforest fires can minimize the rate of forest and land fires in Siak Regency, Riau Province,and the implementation of corporate Sosia; Responciblity (CSR) by PT. PerkebunanNusantara V Sei Artificial is ready in accordance with legal regulations.Keywords: Corporate Sosial Responsibility- Responsibility- Forest Fire